Hydrogen Production: Light‐Driven Sustainable Hydrogen Production Utilizing TiO2 Nanostructures: A Review (Small Methods 1/2019). Issue 1 (7th January 2019) - Cai, Jingsheng; Shen, Jiali; Zhang, Xinnan; Ng, Yun Hau; Huang, Jianying; Guo, Wenxi; Lin, Changjian; Lai, Yuekun
Abstract : To address the environmental and energy problems caused by the rapid consumption of fossil fuels, water splitting for hydrogen production by utilizing semiconductor photocatalysts has been extensively studied as a promising route to produce clean and renewable hydrogen. In article1800184, Yuekun Lai and co‐workers review some main strategies to construct various dimensional TiO2 nanostructures, and modified strategies to enhance solar light harvesting and energy conversion efficiency. Furthermore, the mechanism and potential applications of sustainable photo/photoelectro‐catalytic hydrogen production are comprehensively summarized and discussed.